2011
DOI: 10.1186/1471-230x-11-66
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Hepatitis B Infection-Associated Cirrhosis and Hepatocellular Carcinoma in the Southeast Asian Patients with Portal Vein Thrombosis

Abstract: BackgroundPortal vein thrombosis (PVT) is a rare condition associated with serious morbidity and mortality. The objective of this study was to determine the frequency, clinical presentations, and risk factors of PVT from the set of data firstly collected among the Southeast Asian population.MethodsA retrospective study was undertaken to identify patients diagnosed with thrombosis of the portal system and other abdominal veins. The hospital medical records were retrieved based on the selected ICD-10 codes. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…In a series of 467 patients, thrombosis in several veins has been compared and portal vein thrombosis has been found in 194 (41%) patients. The most common causes of this thrombosis were malignancy in 126 patients (hepatocellular carcinoma, cholangiocellular carcinoma), and infection in 98 patients (hepatitis B, hepatitis C) (11). In the same study, it has been shown that hepatitis C resulted in a higher rate of portal venous thrombosis than hepatitis B (11).…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…In a series of 467 patients, thrombosis in several veins has been compared and portal vein thrombosis has been found in 194 (41%) patients. The most common causes of this thrombosis were malignancy in 126 patients (hepatocellular carcinoma, cholangiocellular carcinoma), and infection in 98 patients (hepatitis B, hepatitis C) (11). In the same study, it has been shown that hepatitis C resulted in a higher rate of portal venous thrombosis than hepatitis B (11).…”
Section: Discussionmentioning
confidence: 48%
“…Chronic hepatitis B virus increases coagulation via anticardiolipin antibodies (ACA) and increases thrombosis formation in the portal vein (12). Portal vein thrombosis was observed in 8 out of 11 patients (72%) with hepatitis B-related hepatocellular carcinoma and ACA (+), whereas out of 54 hepatitis B-related hepatocellular carcinoma and ACA (-), portal vein thrombosis was observed in 14 patients (26%) (11). In our case ACA was (-).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations